If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-76+76=-76x+76
We move all terms to the left:
-76+76-(-76x+76)=0
We add all the numbers together, and all the variables
-(-76x+76)=0
We get rid of parentheses
76x-76=0
We move all terms containing x to the left, all other terms to the right
76x=76
x=76/76
x=1
| x²+12x=364 | | 8x-50=2x+10 | | x-3+4x=19 | | -91=-7(7-x) | | -30=k-17 | | -141=7n-8 | | 164-x=x+60 | | 7(v-7)+5v=35 | | -12=3x-3+6x | | 3x-5=8+2x | | 5(u+6)-7u=18 | | 3/4y-1/2y=5 | | -8x+6-5(x-1)=-5x-(7x-5)+5 | | 21=6x+5=4x | | -(3x•3x)+4=-5 | | 5(w-7)+3w=-27 | | -0.8+4x=0.64 | | 2.5x+2=225 | | 2x-10=74 | | -3-6(x-7)=42-4x | | -1+4x=6x+21 | | x+4/3-x-1/2=4 | | -3p+6(p-2)=4p-8 | | -8-8k=23-(7-4k) | | 3x-10°=100° | | 17/r=102/78 | | 9x-(6x+9)=5x-11 | | -161=-7(8+3n) | | 5x15=40 | | -114=6x+4(2x-4) | | (1/3)x+3=4-x | | j3−8=-7 |